The prevalence of diabetes mellitus among Sami and non-Sami inhabitants of Northern Norway - The SAMINOR 1 Survey (2003-2004) and the SAMINOR 2 Clinical Survey (2012-2014) - Naseribafrouei, Ali; Eliassen, Bent-Martin; Melhus, Marita; Svartberg, Johan; Broderstad, Ann Ragnhild (Rural and Remote Health, 2018)
Source at https://doi.org/10.22605/RRH4623 . Introduction : This study aimed to compare the prevalence of diabetes mellitus (DM) between Sami and non-Sami inhabitants of Northern Norway participating in the SAMINOR 1 Survey and the SAMINOR 2 Clinical Survey, and to track DM prevalence over time. Methods : SAMINOR 1 (2003–2004) and SAMINOR 2 (2012–2014) are cross-sectional, population-based studies that each recruited Sami and non-Sami inhabitants. The data used in this article were restricted to participants aged 40–79 years in 10 municipalities in Northern Norway. Participants completed self-administered questionnaires and underwent clinical examination and blood sampling. Both questionnaire information and non-fasting/random plasma glucose levels were used to ascertain DM. The study included 6288 and 5765 participants with complete data on DM and outcomes, ie 54.6% and 46.3% of the invited samples, respectively. Results : No difference in the prevalence of DM between Sami and non-Sami participants was observed, in either survey. Women had a statistically significantly lower DM prevalence than men in SAMINOR 2. Mean waist-to-height ratio and waist circumference increased substantially in both sexes; mean body mass index increased only slightly in men and remained unchanged in women. The total, age-standardized DM prevalence in SAMINOR 1 and 2 was 10.0% (95% confidence interval (CI) 9.2–10.7) and 11.2% (95%CI 10.4–12.0), respectively, and the proportion of self-reported (ie known) DM increased from 49.2% to 73.0%. In almost the same time span (2004–2015), the use of oral glucose-lowering agents increased. Conclusion : Overall, no ethnic difference was observed in DM prevalence. Overall DM prevalence was high, but did not change significantly from SAMINOR 1 to SAMINOR 2. The percentage of known versus unknown cases of DM increased, as did the prescription of medication for DM between 2004 and 2015.